2003
DOI: 10.1096/fj.02-0424fje
|View full text |Cite
|
Sign up to set email alerts
|

Impaired insulin secretory capacity in mice lacking a functional vitamin D receptor

Abstract: It was the aim of this study to further explore the functional role of vitamin D in the endocrine pancreas. By gene targeting, we have recently generated mice in which a lacZ reporter gene is driven by the endogenous vitamin D receptor (VDR) promoter. These mice express a functionally inactive mutant VDR. Pancreatic islets but not exocrine pancreas cells showed strong lacZ reporter gene expression in mutant mice. To rule out possible influences of hypocalcemia on pancreatic endocrine function, a rescue diet en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
247
3
16

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(282 citation statements)
references
References 25 publications
16
247
3
16
Order By: Relevance
“…Thus, renal failure as the cause of failure to thrive and early death can largely be excluded. Impaired insulin secretion with reduced insulin mRNA expression has been reported in VDR(Ϫ/Ϫ) mice (35), whereas a greater stimulation of insulin secretion by KCl has been reported in CaBP-D28k(Ϫ/Ϫ) mice (36). We found that pancreatic insulin mRNA levels in the double KO mice are normal in comparison with WT mice (data not shown), which rules out insulin as the cause.…”
Section: Table II Physiological Parameters Of 2-month Old Wt Cabp-d2mentioning
confidence: 54%
“…Thus, renal failure as the cause of failure to thrive and early death can largely be excluded. Impaired insulin secretion with reduced insulin mRNA expression has been reported in VDR(Ϫ/Ϫ) mice (35), whereas a greater stimulation of insulin secretion by KCl has been reported in CaBP-D28k(Ϫ/Ϫ) mice (36). We found that pancreatic insulin mRNA levels in the double KO mice are normal in comparison with WT mice (data not shown), which rules out insulin as the cause.…”
Section: Table II Physiological Parameters Of 2-month Old Wt Cabp-d2mentioning
confidence: 54%
“…Their physiological significance at the single-cell level is currently a field of intense study. Typically, rapid 1,25D effects such as transcaltachia in the intestinal epithelium (17) and insulin secretion by ␤-pancreatic cells (18,19) have been studied at the tissue level. In osteoblasts, the bone-forming cells, 1,25D stimulates the production of bone matrix proteins that are constitutively secreted to the extracellular matrix (20,21).…”
mentioning
confidence: 99%
“…[20] Vitamin D 3 facilitates the secretion of insulin from pancreatic beta cells, thus appearing to regulate insulin secretion and therefore vitamin D 3 deficiency may be related to impaired insulin secretion in the diabetes mellitus type 2. [21] Osei et al studies recommend vitamin D 3 supplementation to improve glucose control in type 2 diabetes mellitus patients. [22] In a randomized controlled trial, the administration of 2000 international units (IU) cholecalciferol daily for 16 weeks was found to improve beta cell function in adults at high risk for diabetes, and there was a trend toward attenuating the rise in HbA1c.…”
Section: Discussionmentioning
confidence: 99%